2021
DOI: 10.3390/ijerph18041708
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Electrochemical Removal Mechanism of Oxytetracycline by a Ti/IrO2-Ta2O5 Plate

Abstract: In this study, a Ti/IrO2-Ta2O5 anode was prepared by a hydrothermal method, and the prepared electrode was characterized by techniques such as scanning electron microscopy, X-ray diffraction, and electron dispersive spectroscopy. At the same time, the anode characteristics before and after electrochemical experiments were analyzed. The electrode gradation mechanism of oxytetracycline is discussed. In the whole experimental process, the range of electrolysis conditions was determined by single factor experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…With the increase of the number of cycles, the peaks near 275 and 353 nm gradually weakened. It was speculated that some functional groups were destroyed due to the action of • OH . After 60 s, the well-defined absorption band basically disappeared, which confirmed that the OTC was almost entirely decomposed.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…With the increase of the number of cycles, the peaks near 275 and 353 nm gradually weakened. It was speculated that some functional groups were destroyed due to the action of • OH . After 60 s, the well-defined absorption band basically disappeared, which confirmed that the OTC was almost entirely decomposed.…”
Section: Resultsmentioning
confidence: 93%
“…It was speculated that some functional groups were destroyed due to the action of • OH. 2 After 60 s, the well-defined absorption band basically disappeared, which confirmed that the OTC was almost entirely decomposed. Under the same residence time (60 s), compared with the single degradation experiment (Figure 2), the photocatalytic degradation and reaction rate of the circulation experiment (Figure 3a) were significantly improved.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Compared to the theoretical value of 59.2 mV pH −1 at 25 °C, the slope value of 62.8 mV pH-1 is very similar, which suggests that the OTC oxidation reaction involved a ratio of 1 electrons to protons. The possible mechanism for the electrochemical reactions at the electrode surface is shown in Scheme 1 [ 46 , 47 ].
Scheme 1 Mechanism of detection of oxytetracycline.
…”
Section: Resultsmentioning
confidence: 99%
“… Processes Method Efficiency Refs. Cu-SACs/peroxymonosulfate Peroxymonosulfate, catalyst dose, and initial pH were investigated 96.47% at 60 min 58 plasma-catalytic/graphene-TiO 2 -Fe 3 O 4 nanocomposites catalyst dosage, peak voltage, air flow rate and pH value were investigated 98.1% 59 Electrochemical/Ti/IrO 2 -Ta 2 O 5 anode Electrical current, plate spacing, electrolyte concentration, and solution pH were investigated 99.02% at 20 min 60 Fenton-like rGO in Pd/nZVI/rGO composite rateio, initial concentration of OTC, reaction time, and pH were investigated 96.5% at 60 min 61 UV/peracetic acid pH and a PAA dose were investigated completely removed in 45 min PCO/O 3 pH, reaction time, O 3 concentration, and catalyst dose were investigated at 10 mg/l OTC concentration 96.2% removed at 60 min Current study …”
Section: Resultsmentioning
confidence: 99%